Law Enforcement by Kualanamu Customs and Excise For The Crime of Smuggling Lobster Seeds (Study Of Decision Number 1758/PID.B/2020/PN. LBP) - Bobby Hartanto Sinaga; Rizkan Zulyadi; Ridha Haykal (Asian Journal of Social and Humanities, 2023)
The formulation of the problem is (1) What is the legal regulation regarding customs for baby lobster smuggling according to provisions of regulations – invitations in Indonesia? (2) How is law enforcement carried out by Kualanamu Customs and Excise regarding the crime of smuggling lobster seeds? (3) What are the obstacles Kualanamu Customs and Excise officers face in carrying out law enforcement for the crime of baby lobster smuggling? The research method used is normative juridical. The results of the study show that customs law arrangements for baby lobster smuggling are regulated in Law no. 17 of 2006 concerning customs. Law enforcement is carried out by Customs and Excise officers, namely arresting the perpetrators and transferring them to the Attorney General's Office for further legal proceedings. The obstacle faced by Customs and Excise officials is that very often unscrupulous law enforcement officials and unscrupulous airline officers who work at airports are involved in criminal cases of smuggling and assist perpetrators who will try to bring prohibited items to pass from the customs area. This has further reduced public trust in law enforcers and this is an obstacle for law enforcers in general. The conclusion of this study is that Kualanamu Customs and Excise officers as customs law enforcers work together with other law enforcement officers in accordance with statutory regulations. The suggestion from this thesis is for Kualanamu Customs and Excise officers to become officers who really carry out law enforcement in the field of customs, so that in the future there will be no more smuggling cases that occur within the scope of Kualanamu airport carried out by the public or unscrupulous officers working at Kualanamu Airport